Chelation therapy in children - M. V. Krasolnikova (Медицинский совет, 2016)
Iron overload (RV) is a condition caused by excessive intake of iron, and in the absence of the specific mechanisms for its excretion - excessive accumulation in tissues and their subsequent lesion leading to functional organ failure [1]. This condition most commonly occurs as a result of regular replacement therapy with erythrocyte mass in the treatment of various anemias. According to statistics, about 500 sick children and 2 000 adults develops post-transfusion RV in Russia in every year [2]. It develops in the context of hereditary anemia (major and intermediate forms of beta-thalassemia, other hemoglobinopathies, severe membrane and enzyme defects, congenital sideroblastic and dyserythropoetic anemia, constitutional hypo- and aplastic anemia) or acquired diseases (acquired aplastic anemia, myelodysplastic syndrome (MDS), myelofibrosis, etc.). [3--5].